Multinational enterprises, local firms, and employee human rights violation in the workplace: Evidence from Mexico. Issue 3 (16th September 2019) - Colovic, Ana; Escobar, Octavio R.; Lamotte, Olivier; Meschi, Pierre-Xavier
Abstract : Purpose: This paper aims to investigate whether multinational enterprises (MNEs) are more or less likely than local firms to violate their employees' human rights in emerging economies, whether regional institutional pressures influence the likelihood of violating employee human rights and whether the density of MNEs in a region affects the likelihood of employees' human rights violation by local firms. Design/methodology/approach: Building on neo-institutional theory, this paper hypothesizes that, in an emerging economy, MNEs violate their employees' human rights significantly less than local firms do. Moreover, it is hypothesized that the quality of regional institutions only influences the social behavior of local firms toward their employees. In addition, it is hypothesized that the density of MNEs in a region has a positive effect on local firms' attitudes toward employee human rights. These hypotheses are examined using a sample of 1, 211, 638 respondent–year observations in 32 Mexican regions between 2005 and 2014. Findings: This paper shows that MNEs are less likely to violate their employees' human rights than local firms are. It also provides evidence that regional institutions do not influence MNE behavior toward employee human rights violation, but affect local firms. Furthermore, contrary to what was hypothesized, the density of MNEs in a region has a negative rather than positive influence on local firms' respect of employee human rights. Originality/value: This paper advances understanding of the behavior of MNEs in an emerging economy setting and contributes to the ongoing debate in the literature on their social impact.